Cytotoxic and genotoxic studies of essential oil from Rosa damascene Mill., Kashan, Iran - Mohammad Shokrzadeh; Emran Habibi; Mona Modanloo (Medicinski glasnik, 2017)
Aim: Rosa damascene Mill. belongs to the family of Roseaceae and its essential oil is produced in large amounts in Iran. The wide application of rose oil has raised questions about potential adverse health effects. We have investigated cytotoxic activity and genotoxic effects of Rosa oil from Kashan, Iran. Methods: The cytotoxic effect and IC50 of the essential oil on the cell lines was studied followed by MTT assay. In this assay mitochondrial oxidoreductase enzymes with reducing the tetrazolium dye MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) reflect the number of viable cells. Genotoxic effect of the oil was evaluated by micronucleus assay by evaluating produced micronuclei due to cytogenetic damage in binucleated lymphocytes. Results: The results showed that essential oil significantly had cytotoxic and genotoxic effects at doses over 10µg/mL (p<0.05). Also, essential oil of Rose showed lower IC50 in cancer cell line (A549) in comparison with the normal cell line (NIH3T3). Conclusion: Cytotoxic and genotoxic properties of essential oil of Rose in Kashan, Iran, are safe at a dose of 10µg/mL. Also, a good cytotoxic effect was shown and could be introduced as an anticancer compound. Further studies are needed with regard to anti-cancer effects of Rose essential oil.
Keywords: micronucleus assay; MTT; Rose oil